Comparison of Two Enzyme-Linked Immunosorbent Assays and One Rapid Immunoblot Assay for Detection of Herpes Simplex Virus Type 2-Specific Antibodies in Serum - Groen, Jan (American Society for Microbiology, 1998)
The sensitivities and specificities of three immunoassays for the detection of herpes simplex virus type 2 (HSV-2)-specific immunoglobulin G antibodies in serum, including the one-strip rapid immunoblot assay (RIBA; Chiron Corporation) and two indirect enzyme immunosorbent assays (EIA; Gull Laboratories and Centocor), were compared by testing a panel of 1,250 serum samples from individuals attending an outpatient clinic for sexually transmitted diseases. A qualitative agreement among the three assays was observed with 1,080 serum samples (86.4%); 291 of the serum samples (23.3%) were positive, 789 samples (63.1%) were negative, and 170 serum samples (13.6%) gave a discordant result. Results were considered conclusive when a concordant result was obtained with two of three assays. The sensitivities and specificities of the RIBA, the Gull EIA, and the Centocor EIA proved to be 99.2, 99.7, and 89.9% and 97.1, 96.7, and 99.3%, respectively. These results indicate that the Chiron RIBA and the Gull EIA are especially useful and reliable for the detection of HSV-2-specific antibodies in serum.